Strategi Pengelolaan Kekayaan Menggunakan Wealth Management Dalam Upaya Mengembangkan Sarana Dan Prasarana Di Pondok Pesantren Sunan Drajat - Ahmad Khoiron Minan (STAI Ma'had Aly Al-Hikam Malang, 2022)
This research was conducted against the background of important asset and wealth management in educational institutions, especially Islamic educational institutions. This is because many Islamic educational institutions do not know the potential of their assets. Asset management using wealth management with Robert's quadrant cashflow approach. T. Kiyosaki can be used as a reference in mapping the assets owned by Islamic educational institutions, to then be developed and can have an impact on aspects of education support, one of which is wealth management facilities and infrastructure conducted in sunan drajat boarding school is done with the aim that the foundation can meet the needs independently without depending on other parties, especially in the development of educational facilities and infrastructure. This study includes qualitative research. Data is collected through interviews, documentation and observations. The results of the study showed that: 1) Wealth management, especially finance is carried out with a closed-transparent principle, with the division between educational financial institutions (BKK) and business financial institutions (Perkom) while holding the concept of financial management and financial management principles. 2) Wealth management conducted in sunan drajat boarding school using cashflow quadrant submitted by Robert T. Kyoosakai that has been modified in accordance with the educational environment, shows that Sunan Drajat boarding school is close to financial freedom in the management of his wealth. 3) The impact of Wealth Management in the development of educational facilities and infrastructure in Pondok Pesantren Sunan Drajat, among others, the first, the completeness of educational facilities and infrastructure. Secondly the maintenance of educational facilities and infrastructure and third, the effective use of educational facilities and infrastructure